Analisis Reaksi Pasar Atas Pengumuman Cum Dividen (Studi Pada Saham Yang Terdaftar di Jakarta Islamic Index Tahun 2012-2013) - Herlambang, Leo (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
Cash dividends is one of the corporate action that contains information related to the companys performance and signal to investors about the companys prospects. This internal information of the company will affect the investment decisions of investors. The reaction of investors in the market will lead to changes in demand and supply of common stocks around the cum-dividend date. This study aims to determine the reaction of the Islamic capital market as indicated by the change in abnormal return around the cum-dividend date.This study uses event study approach, carried out on 30 issuers listed on the JII during 2012-2013 who pay cash dividends. The period of observation in this study was for 29 days, starting 14 days before the event date to 14 days after the event date. This study uses one-sample test in hypothesis testing.The results based on the statistical test showed significant variables caar AAR and on some days around cum dividedn date. These results indicate that there is a market reaction around cum dividend.